Innovation and the arts : the value of humanities studies for business - Formica, Piero; Edmondson, John (Emerald Publishing Limited, 2020)
We live in the Age of Knowledge but we are heading towards the Age of Imagination. However, our current education systems still divide arts and business, juxtaposing them as different worlds, apparently ignoring the essential truth that imagination is the springboard of innovation. For business to continue to evolve, the barriers to creativity and innovation must be lowered. In Innovation and the Arts: The Value of Humanities Studies for Business, editors Piero Formica and John Edmondson bring together a cast of expert contributors to explore how arts education can transform future business and social endeavours by developing empathy and enhancing skills frequently identified as lacking in graduates entering the workplace. Looking at arts and humanities across the broad spectrum of business and social innovation, and in the context of business education, examples of entrepreneurial and innovative developments, and the nature of the innovative mind, the contributors show how underdeveloped empathy and creativity constrain innovation. Art is disruptive, and innovation requires disruption to thrive. By dwelling on the need for the convergence of business, innovation and the arts, Innovation and the Arts highlights the inestimable value of lowering the psychological, organizational and institutional barriers that keep them apart. For educators and practitioners, this is an in-depth discussion designed to stimulate awareness of the issues facing business education.
Prelims -- 1. Business, innovation and the arts : the golden encounter / Piero Formica -- 2. The golden path toward the arts in/with business / Tatiana Chemi -- 3. Teaching intangibles - uncertainty and imperfection and the institutional challenge of the unmeasurable / John Edmondson -- 4. On regarding the value of aesthetics for entrepreneurship / Jay Mitra -- 5. The true value of 'doing well' economically / Morten Tønnessen -- 6. Beyond the 'great derangement': will the humanities lead ecological transition? / Fabio Montagnino -- 7. Move slow and nurture things: wise creativity and human-centred values in a world that idolizes disruption / Danah Henriksen and Punya Mishra -- 8. How businesses can benefit from collaborating with the arts / Peter Robbins -- 9. The arts as an economic driver in an era of exponential technologies: a Silicon Valley entrepreneur's perspective / Sheridan Tatsuno -- 10. Leadership in business, innovation and art : lessons learnt from an orchestra conductor / Edna Pasher, Roni Porat, Yaara Turjeman-Levi, Mor Harir and Yael Caspi.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Business education; Humanities -- Economic aspects; Business & Economics -- Education; Industrial or vocational training